Immersive Heritage: Exploring Srivijaya's Historical Legacy Through Virtual Reality in Digital Communication - Zinaida, Rahma Santhi; Amin, Zaid; Apriani , Mira (Universitas Muhammdiyah Yogyakarta, 2025)
Srivijaya is the splendor of the past that shaped world civilization, but the younger generation is now starting to forget the history. History education is important to be a compulsory subject and course because it contains content rich in moral messages of the nation and state, such as nationalism, patriotism, greatness, and integrity, and is even meaningful in contributing to the formation of the imagination of a modern nation-state. There is a value from the struggle of ancestors in the past to be used as an example and reflection of future generations. Data related to Srivijaya, such as research results, books, journals, articles, and historical heritage sites such as museums, are straightforward to obtain literature via the internet; however, the existing data seems scattered and not neatly integrated, for this research is intended to integrate various data so that history is not forgotten and eroded by the development of the times, in fact, the more developed an era, the more its historical roots must be preserved. The urgency of this research is how to align technological advances with preserving the history of Srivijaya; one of the big ideas is to create the Srivijaya Digital Encyclopedia (Srivijayapedia). The formulation of the problem that is the aim of this research is How to build a Digital Encyclopedia as a novelty related to Srivijaya (Srivijayapedia) as an exploration of the history of Srivijaya's glory through digital communication media Virtual Reality based on Immersive Technology. This research uses the theory of digital communication and immersive technology using the mixed research method, where the qualitative method is used for data search using observation and interviews for the encyclopedia's content. In contrast, the quantitative method will be used during the virtual reality experiment. The output of this research is the prototype of the Srivijaya Encyclopedia (Srivijayapedia), which has been added to virtual reality media to make it more communicative and interactive; this idea can contribute to further research.